Establishment of a Selective Liver Lobe Tumor-Bearing Mouse Model of Colorectal Cancer - Zheqi Han MS; Biying Qiu MS; Lin Li MS; Jianhua Yu MD; Zhiyang Zhu MS (Technology in Cancer Research & Treatment, 2023)
Purpose Colorectal cancer is one of the most common causes of cancer-related death, and its main site of metastasis is the liver. The surgical method used for metastases of colorectal cancer in the liver varies according to the lobe affected, as does the prognosis. However, there is a lack of relevant basic research. Therefore, a good animal model is needed for basic studies of metastases from colorectal cancer to the different lobes of the liver. Methods A CT26 colon cancer cell line transfected with a virus expressing green fluorescent protein was inoculated into BALB/C mice via the spleen. Tumor formation in the liver lobes was observed under a fluorescence microscope according to which portal vein branch was ligated and according to clamping time. The differential formation of metastatic lesions in the different lobes was then compared with physical anatomy. Serum samples were used to detect the changes in liver function postoperatively. Results Ligation and resection of the spleen 1 min after injection of the CT26 cells and release of the vessel clamp 1 min after splenectomy created an ideal tumor-bearing mouse model with little effect on liver function. Selective clamping of each portal vein branch and splenic injection of a CT26 cell line successfully established a selective liver lobe tumor-bearing model of colorectal cancer with distinct characteristics. Conclusion This model provides an opportunity for investigation of the mechanisms of metastasis of colorectal cancer to different lobes of the liver and may provide a basis for clinical treatment.